Measuring critical thinking skills of undergraduate students in Universiti Putra Malaysia - Ghadi, Ibrahim Nazem; Abu Bakar, Kamariah; Alwi, Nor Hayati; Othman, Othman (Asian Economic and Social Society, 2013)
This paper conducted a study to measure the Critical Thinking Skills of undergraduate students at Universiti Putra Malaysia based on a pilot study involving 433 students randomly selected. The main purpose of this paper is to describe the process in determining the suitability of all the items in the CTS instrument which would be used in the actual study. Four factors of the CTS (Analysis, Evaluation, Deduction and Induction) were tested for their validity and reliability. The CTS knowledge test comprised of 22 multiple-choice questions with two alternatives. All the four factors in the instrument were adapted from (Goel et al., 1997), (Choi et al., 2007), (Stanovich and West, 1997). Results from the pilot study have shown that the items to measure CTS have good discriminating quality, validity and reliability